Self‐Regulated Glucose‐Sensitive Neoglycoenzyme‐Capped Mesoporous Silica Nanoparticles for Insulin Delivery. Issue 6 (19th December 2016) - Oroval, Mar; Díez, Paula; Aznar, Elena; Coll, Carmen; Marcos, María Dolores; Sancenón, Félix; Villalonga, Reynaldo; Martínez‐Máñez, Ramón
Abstract: We describe herein the preparation of glucose‐sensitive capped mesoporous silica nanoparticles for insulin delivery. The new material consists of an expanded‐pore nanometric silica support grafted with 1‐propyl‐1‐ H ‐benzimidazole groups, loaded with fluorescein isothiocyanate‐labeled insulin (FITC‐Ins) and capped by the formation of inclusion complexes between cyclodextrin‐modified glucose oxidase (CD‐GOx) and the benzimidazole groups grafted on the mesoporous support. Insulin delivery from the gated material in simulated blood plasma was assessed upon addition of glucose. Glucose is transformed by GOx into gluconic acid, which promoted the dethreading of the benzimidazole–CD‐GOx inclusion complexes, allowing cargo release. Small quantities of this support would be needed to release the amount of insulin necessary to decrease diabetic blood glucose concentrations to regular levels. Abstract : Controlled delivery : A novel nanoplatform combining diagnostic and drug delivery capabilities is presented. The capped system is based on a nanometric silica support loaded with fluorescein isothiocyanate‐labeled insulin (FITC‐Ins) and capped with cyclodextrin‐modified glucose oxidase (CD‐GOx). This nanosystem is able to release the entrapped FITC‐Ins in a controlled manner owing to the specific enzymatic reaction between glucose and GOx.